Edward Hajduk - Zauważenia = Edward Hajduk - The Remarks - Hajduk, Barbara; Hajduk, Damian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of "Zauważenia" ("The Remarks") is a sociologist, educator, logician, philosopher, methodologist in social sciences. His miniatures written in the period 2008-2014, some of which we publish here, are the subplot of the author's main scientific interests, often mocking and self-ironical character.
Keywords: Hajduk, Edward (1932-2015)